PENGARUH BRAND IMAGE TERHADAP REPUTASI BANK SYARIAH INDONESIA - Muhamad Dika Fachri Fachri; Siti Umul Muhadanah (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
Amidst the rapid development of Islamic banking in Indonesia, a bank's reputation is determined by its brand image in addition to its financial performance. This study aims to explore the impact of brand image on the reputation of Bank Syariah Indonesia (BSI) located in Serang City. This study uses a quantitative approach with a survey technique. The primary data were obtained through questionnaires using a Likert scale to 61 respondents. Analysis was conducted using simple linear regression using STATA software. The findings of this study indicate that brand image has a significant influence on BSI's reputation. The coefficient of determination (R²) value of 0.3879 indicates that brand image explains 38.79% of the variation in reputation, while 61.21% is influenced by other factors outside the existing model. The positive regression coefficient indicates that an increase in brand image is directly proportional to an increase in the bank's reputation. These results emphasize that the reputation of Islamic banks is not only built by brand image, but also by service quality, client satisfaction, and communication that is in line with sharia principles. Brand image has been shown to significantly influence BSI's reputation in Serang City, but it is not the sole determining factor.